Psychological well being in the age of resource scarcity: An analysis of time and money donation behaviors - Ayar, Bahadır (Graduate School, 2025)
One of the inevitable realities individuals face in their daily lives is having limited resources. This situation, referred to as resource scarcity, can be defined as having fewer resources than needed to meet one's needs and wants. The resource scarcity encountered by individuals can be assessed on both macro and micro levels. On a macro level, the scarcity of water and food supply due to high levels of drought in various regions of the world can be considered resource scarcity. On a micro level, individuals may feel pressure due to limited financial income to meet personal needs and time constraints on daily activities. This thesis focuses on micro-level resource scarcity, emphasizing individuals' perceptions of time and money as scarce resources. It is clear that a multitude of factors influence consumer behavior. Previous studies have shown that consumer behavior is shaped by individual, situational, economic, psychological, sociological, and other factors. In these studies, resource scarcity has been considered a factor affecting consumer psychology and behavior, revealing its impacts on individuals' cognitions, attitudes, and behaviors. It is known that individuals with limited resources experience increased stress levels, feel negative emotions, and generally have decreased life satisfaction. Resource scarcity adversely affects consumers' decision-making processes, leading to observable changes in their cognitions. Moreover, when faced with resource scarcity, consumers are known to use their existing resources more consciously and experience a fear of missing out. While engaging in consumption activities for themselves, individuals also allocate resources for those in need and to improve societal welfare. When considered consumer behavior, this behavior, termed donating or charitable giving, highlights the importance of understanding the role of resource scarcity in donation behavior. Individuals tend to donate by giving money and time to nonprofit organizations providing access to aid products or services to needy people. The fact that time and money, the two primary sources of giving behavior for today's individuals, are limited resources reveals the importance of resource scarcity on giving behavior. Time and money are perceived differently by individuals due to their various characteristics. For instance, money is more accessible to count, save, and touch than time. While time is associated with an emotional mindset in consumers' minds, money is related to a financial value-based mindset. When examined within the framework of construal level theory, money is perceived concretely by individuals, whereas time is perceived abstractly. However, considering that resource scarcity affects cognitive processes, it is crucial to understand how perceptions of time and money differ during donation compared to situations where scarcity is not felt. Given that individual donors predominantly make donations to nonprofit organizations understanding the perceptions of scarce resources like money and time during the donation process can provide insights into how relevant organizations should approach their current and potential donors. Regardless of the amount of resources individuals possess, individual and organizational factors affect donation behavior. Some of these factors are the perceived donation efficacy and organizational trustworthiness. Since scarce resources are attributed greater value by individuals, organizations' trustworthiness and perceived donation efficacy gain importance when these resources are donated. Additionally, donating scarce resources with greater attributed value makes donors feel better about themselves. This study examines trust in the institution and perceived donation effectiveness as variables affecting the relationship between psychological well-being and donation intention. This thesis employed experimental design and in-depth interviews to answer the research questions. Study 1a investigates how donors perceive money and time within the framework of construal level theory in situations without any scarcity manipulation. Study 1b explores how donors exposed to resource scarcity manipulation perceive money and time. Study 2 focuses on the psychological well-being levels obtained by individuals donating their scarce resources. It reveals the difference in psychological well-being levels obtained based on the type of resources donated. Study 3 examines the moderating effect of organizational trustworthiness and perceived donation efficacy on the relationship between the psychological well-being levels of individuals donating their scarce resources and their donation intentions. Through in-depth interviews, the aim was to identify the reason behind the insignificant moderating effect of organizational trustworthiness and perceived donation effectiveness on the relationship between psychological well-being levels and donation intentions. The results indicate that without a scarcity reminder, donors perceive time on an abstract level and money on a concrete level. When exposed to resource scarcity manipulation, the level of abstraction in perceiving time and money increases.
Kaynak kıtlığı çağında psikolojik iyi oluş: Zaman ve para bağışlama davranışlarının bir analizi
Thesis (Ph.D.) -- Istanbul Technical University, Graduate School, 2025
Keywords: resource scarcity; kaynak kıtlığı; donation; bağış; time management; zaman yönetimi